Effect of Non-Pharmacologic Vitamin D Status Correction on Circulating Bone Markers in Healthy Overweight and Obese Saudis - Mona Fouda; Sobhy M. Yakout; Yousef Al-Saleh; Abdulaziz Al-Othman; Khalid M. Alkharfy; Nasser M. Al-Daghri; Shaun Sabico (Molecules, 2013)
While moderate to severe vitamin D deficiency is prevalent in Saudi Arabia, skeletal effects associated with this deficiency are not common in this population. In this interventional study we measured the effects of improving vitamin D status on bone biochemical markers in overweight and obese adult Saudis. A total of 47 volunteers (21 males, 26 females) out of the initial 95 subjects were given verbal advice to expose themselves to sunlight for 5–30 min twice weekly and were encouraged to increase their intake of vitamin D–rich foods. Serum 25(OH)D, osteocalcin, and type 1 collagen cross-linked C-telopeptide (CTx), were measured at baseline and after one year. A significant decrease in the prevalence of vitamin D deficiency was observed (44% to 27%) after one year follow-up (p = 0.025). Also, a parallel significant increase in osteocalcin and a decrease in CTX and osteoprotegerin were observed. The results suggest that a modest increase in vitamin D levels among overweight and obese subjects through the promotion of lifestyle changes for one year have marginal effects in bone turnover markers as well as obesity itself.